The generation and suspension of meaning in Dostoevsky’s Demons - Bamba, Satoshi (Studies in East European thought, 2025)
This paper examines the relationship between the generation and suspension of meaning in Dostoevsky’s Demons with reference to Bakhtin’s thesis that one’s meaning is defined by someone else’s answer. By generation I mean both the generational conflict between fathers and children and the generative power of language. It is the division between what one says and what one means that troubles Stavrogin. He has his authorship usurped by others and is not in control of his own discourse. Although the document headed “From Stavrogin” in the unpublished chapter “At Tikhon’s” has traditionally been called a confession by critics, that is misleading, for, as the narrator points, the pages look very much like a political tract, and what is at stake in his dialogue with Tikhon is the very question: is it a confession or not? This document also raises questions about the authenticity of signatures, as does Prince Myshkin’s counterfeiting of someone else’s signature in The Idiot .